Analysis of Land Use Change in Pagu River Subdistrict, South Solok Regency in 2010 and 2020 - Muhammad Jhodi Linanto; Ernawati Ernawati (Jurnal Kependudukan dan Pembangunan Lingkungan, 2021)
Land use changes are caused by the needs of local people for the survival of life. This resulted in increased land needs both for settlements and for economic source land. The purpose of this study is to 1) Know the change in land use in Sungai Pagu Subdistrict in 2010 and 2020, 2) Know the extent of changes in the use of rice fields in Sungai Pagu District in 2010-2020. In this study, the classification process was carried out using the Object Based Image Analysis method. From the results of the analysis of land use changes in The Pagu River Subdistrict in the period 2010 to 2020 it is known that the largest land use changes occurred in high land forests. Primary High Density which experienced the largest decrease in land area as much as 11,398 ha, in addition there was a change in the area of use of rice fields, both from other land uses that turned into rice fields, and initially rice fields turned into other land allocations. Shrubbery becomes the largest land use converted into rice fields with a change area of 339.67 hectares.